O discurso da "vidência": cruzamento vocal na interlocução entre "céu e terra" - Martins, Lenice Amélia de Sá (2007)
This paper consists of an analysis of the polyphonic interplay embodied in the discourse of clairvoyance . In preparing it, we sought to use as a foundation the propositions set out in Enunciation Theory and Discourse Analysis, which conceive of language as an activity performed by concrete subjects within a particular time and space. The documentary sources that furnished the material for this examination are works representing the product of this dialog between heaven and earth. The corpus taken from such sources is comprised of: four texts relating to the apparitions at Fatima (Portugal); two relating to those at Angüera (Bahia); one about those in Itaperuna (Rio de Janeiro); and the last one concerning the incidents of clairvoyance in Jacareí (São Paulo). With this exercise, we aim especially to demonstrate, in terms of linguistic materiality, the way in which the polyphony is constituted in this interlocution between two disparate spheres: the material and the spiritual. Going deeper into this discursive action, we were able to perceive that it is made up of a vocal intertwining formed by the multiplication of subjects (polyphony strictly speaking, according to Ducrot, 1987) and by external voices originating with Holy Scripture and the Catholic Church (intertextuality). The study further revealed that these discourses are marked by a perceptible identity as regards ideological aspects since all of them, whether produced in Brazilian territory or coming from abroad, reflect the ideology of the Roman Catholic Apostolic Church. The unveiling of the intimate link between the voices echoing from these two dissymmetric worlds finds justification in that they make it possible to amplify the study of religious discourse, of which this topic is a part, namely the discourse of clairvoyance.